Compendious Summary of Blockchain - Kingslin, Sumathy; Zahra, Rafath (International Journal of Computer Sciences and Engineering, 2025)
Where there is technology there is always a scope for innovation. Blockchain technology is one such innovation that provides a decentralized solution for storage and immutable transactions that is hardly possible to fake. Blockchain is a subject undergoing intense study that has gained universal attention being the foundation of the most happening cryptocurrency. It is a distributed ledger that uses the appropriate consensus algorithm for secure transactions and records them all in an immutable chain of blocks hence forming a blockchain. Each block in a blockchain can be considered as page of a record that includes all the necessary details of any transaction. The transactions could be of any type based on the application the blockchain technology is being used for. The security and integrity of blockchain is achieved by using hashing and consensus algorithm. Hash is a unique number that determines a specific block. Each block contains the hash of the current block and also the hash of the previous block, any tampering with a block affects the validity of the following blocks making them invalid. Nodes in a blockchain are interconnected using peer-to-peer network and play a decisive role to validate any new transaction. Nodes come to a consensus using complex mathematical calculations after which the validated transaction records are added to the blockchain. Blocks that are once added to a blockchain can never be modified. A single node or a single network cannot control the entire database providing security in a trust less network. These spectacular features of blockchain has gained popularity in various fields other than cryptocurrency, to name a few real-estate, supply chain management and health care etc., This paper gives a compendious summary of blockchain with an overview of its fundamentals, its working and its diverse applications.